2010
DOI: 10.4103/0970-9290.70804
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood groups and Rhesus factor: An exploring link to periodontal diseases

Abstract: The genetic factors may alter the oral ecology and the process of periodontal disease. These data are suggestive of a broad correlation between periodontal diseases and blood groups, which may act as risk predictors for periodontal diseases. This will make it possible to better-understand the risk factors of diseases of the periodontal tissues and to predict the effective methods of prevention and treatment of periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 1 publication
5
36
0
Order By: Relevance
“…Patients with blood group B appeared to be at greater risk of developing more severe forms of periodontitis. Koregol, et al [12], stated that blood group type A showed a significantly higher percentage in the gingivitis group, blood group O showed a higher incidence in the periodontal group. The blood group AB showed the least percentage of periodontal diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Patients with blood group B appeared to be at greater risk of developing more severe forms of periodontitis. Koregol, et al [12], stated that blood group type A showed a significantly higher percentage in the gingivitis group, blood group O showed a higher incidence in the periodontal group. The blood group AB showed the least percentage of periodontal diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Surprisingly, limited number of studies has been conducted to determine the association of ABO blood group with periodontal diseases. [ 17 18 19 20 21 22 23 24 25 26 27 ] Some researchers claimed that there was relationship between ABO blood group and periodontal diseases, whereas others could not find any, which could be attributed to the geographic diversity in the population groups. The studies by Koregol et al .…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Koregol et al . [ 18 ] and Demir et al . [ 19 ] showed that gingivitis was more common in blood Group A and periodontitis was more common in blood Group O, while another study by Al Ghamdi[ 20 ] showed that blood Group B was found to be at greater risk for periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…[20] in a study on 1220 subjects in South India concluded that blood group A formed a significantly higher percentage in the gingivitis group and blood group O formed a higher percentage in the periodontitis group. The blood group AB showed the least percentage of periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%